Scale validation methodology - Theodosopoulou, Eleni; Raftopoulos, Vasilios (My University, 2002)
The systematic use of psychometric scales, in psychology and psychiatry, but also in other research initiatives, necessitates the development and use of research methodology that assures validity and reliability of these scales. The aim of this paper is to describe such methodology, using examples from patient satisfaction literature.
Keywords: Factor analysis; Patient satisfaction; Scale validation; Validity; Reliability